2021
DOI: 10.1155/2021/6633563
|View full text |Cite
|
Sign up to set email alerts
|

Shared Molecular Mechanisms between Alzheimer’s Disease and Periodontitis Revealed by Transcriptomic Analysis

Abstract: Objective. To investigate the genetic crosstalk mechanisms that link periodontitis and Alzheimer’s disease (AD). Background. Periodontitis, a common oral infectious disease, is associated with Alzheimer’s disease (AD) and considered a putative contributory factor to its progression. However, a comprehensive investigation of potential shared genetic mechanisms between these diseases has not yet been reported. Methods. Gene expression datasets related to periodontitis were downloaded from the Gene Expression Omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…FCGR3A is also named as CD16 which has been identified as the pathogenic factor to participate in the deterioration of atherosclerosis, and the study has indicated that FCGR3A may be connected with ischemic stroke [ 12 , 28 ]. Besides, several studies have shown that both FCGR3A and MAPK pathway exhibited significant aberrant levels in some diseases such as chronic constriction and Periodontitis [ 29 , 30 ], while few studies have indicated the connection of FCGR3A and MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…FCGR3A is also named as CD16 which has been identified as the pathogenic factor to participate in the deterioration of atherosclerosis, and the study has indicated that FCGR3A may be connected with ischemic stroke [ 12 , 28 ]. Besides, several studies have shown that both FCGR3A and MAPK pathway exhibited significant aberrant levels in some diseases such as chronic constriction and Periodontitis [ 29 , 30 ], while few studies have indicated the connection of FCGR3A and MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first analysis of cross-talk mechanisms between periimplantitis and RA on the transcriptomic level. Bioinformatics analysis has been applied for several other diseases and conditions, such as periodontitis and Alzheimer’s disease, periodontitis and oral cancer, or between periimplantitis and type 2 diabetes mellitus ( 20 , 21 , 53 ). Therefore, this method appears reasonable for the current study aim, i.e., detecting the cross-talk between periimplantitis and RA to reveal whether there is a similarity regarding auto-inflammation between the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the molecular mechanism, including genetics and epigenetics between oral and systemic diseases, has been successfully explored by bioinformatics analysis. So an interlink between periodontitis and Alzheimer’s disease, or between periimplantitis and type 2 diabetes mellitus, has been detected ( 20 , 21 ). Accordingly, this current study used bioinformatics to reveal the cross-talk mechanisms between periimplantitis and RA at the transcriptomic level.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of crosstalk genes, neuropeptides, and pathways was very comprehensive and is up until now unique in literature. Other working groups [ 31 , 32 ] have already successfully applied similar methodology previously to reveal the link between periodontal and systemic diseases. However, several limitations exist.…”
Section: Discussionmentioning
confidence: 99%